Protective murine monoclonal antibodies to Cryptococcus neoformans. - Mukherjee, J (1992)
Several murine monoclonal antibodies (MAbs) specific for the capsular glucuronoxylomannan of Cryptococcus neoformans were studied for their capacity to confer protection when passively administered to lethally infected mice. The MAb group studied recognized at least three distinct epitopes and included immunoglobulin M (IgM), IgG3, IgG1, and IgA isotypes. The protection model used A/J and BALB/c mice infected intraperitoneally with 10(8) cryptococci. The MAbs were administered either immediately preceding or, in one experiment, 24 to 48 h prior to infection. Protective efficacy was assessed by the ability of passively administered MAbs to prolong the survival of lethally infected mice. Three IgM MAbs, each of which recognized a distinct epitope, were able to prolong survival of lethally infected mice to different extents. A set of IgM, IgG3, IgG1 and IgA MAbs which utilize the same immunoglobulin gene elements and were derived from the same B-cell clone exhibited significant class differences in protective efficacy with IgA, IgG1 > IgM > IgG3. The results confirm that protective MAbs against C. neoformans capsular polysaccharide exist and strongly suggest that both epitope specificity and isotype are important determinants of protective efficacy.